Legal Effectiveness in the Application of Halal Product Assurance Certification to MSME Business Actors According to Law Number 33 of 2014 concerning Halal Product Assurance - Wiwik Sri Widiarty (Publikasi Indonesia, 2024)
Law Number 33 of 2014 concerning Halal Product Assurance (JPH Law) aims to protect consumers and increase the competitive ability of Indonesian halal products in the world market, which is included in the aspects listed in the JPH Law, namely the obligation for business actors to obtain halal certificates for goods that business actors produce and trade. The focus of the study aims to evaluate the extent of legal effectiveness in the application of halal product assurance certification by MSME business actors. The research method used is qualitative with techniques in collecting data, namely literature studies. After the data is collected, data analysis is carried out which includes the stages of data simplification, data presentation and conclusion making. The conclusion of the study explains that the effectiveness of the law in implementing halal product assurance certification for MSME business actors is still at a low level. Several obstacles were identified, such as lack of knowledge about the JPH Law and the halal certification process, the relatively expensive cost of halal certification, the halal certification process which is considered complicated and convoluted and lack of assistance and socialization from the government.